2022
DOI: 10.1007/s00784-022-04809-y
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of five different 3D printing workflows for dental models comparing industrial and dental desktop printers

Abstract: Objectives The aim of this study was to evaluate the accuracy, in terms of trueness and precision, of printed models using five different industrial and dental desktop 3D printers. Materials and methods Full-arch digital models with scanbodies of 15 patients were printed with five different 3D printers. The industrial printers were 3D system Project MJP2500 (3DS) and Objet30 OrthoDesk (Obj). The dental desktop printers were NextDent 5100 (ND), Formlabs Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The study concluded that these printers are suitable for clinical practice, exhibiting overall errors within clinically acceptable levels of under 100 microns. 32 Morón-Conejo et al 33 conducted a comparative analysis of the accuracy, trueness, and precision of five different 3D printers utilized for full-arch models of patients. This included both industrial and dental desktop printers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that these printers are suitable for clinical practice, exhibiting overall errors within clinically acceptable levels of under 100 microns. 32 Morón-Conejo et al 33 conducted a comparative analysis of the accuracy, trueness, and precision of five different 3D printers utilized for full-arch models of patients. This included both industrial and dental desktop printers.…”
Section: Discussionmentioning
confidence: 99%
“…Morón‐Conejo et al. 33 conducted a comparative analysis of the accuracy, trueness, and precision of five different 3D printers utilized for full‐arch models of patients. This included both industrial and dental desktop printers.…”
Section: Discussionmentioning
confidence: 99%
“…The SLA printer likely involves applying a sufficient output of UV light to the vat using a laser beam emitter, and the DLP printer projects a strong output of UV light through a DLP engine, whereas the LCD printer relies on the LED components of the panel, resulting in the observed differences. Morón-Conejo et al compared the accuracy performance of industrial and dental desktop 3D printers and found comparable results for Form 2, a low-budget SLA device [ 43 ]. In a study evaluating the trueness and dimensional stability of abutment die models, the Shuffle, economic LCD 3D printer group showed the least trueness but was still comparable to the stone dies group [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although different types of printers have their relative advantages and disadvantages, it is important to recognize that the accuracy of the final printed product depends on the combination of the printing technology, the particular printer that is used, and the selected material. 5,6 Industrial printers have been reported to be superior to dental desktop printers, 5 and material jetting printers have been reported to be superior to SLA or DLP printers. 6 However, some of these may introduce a level of error that is not clinically relevant.…”
mentioning
confidence: 99%
“…5,6 Industrial printers have been reported to be superior to dental desktop printers, 5 and material jetting printers have been reported to be superior to SLA or DLP printers. 6 However, some of these may introduce a level of error that is not clinically relevant.…”
mentioning
confidence: 99%